Psychiatric disorders in Chinese immigrants during the 19th century. Second part: Life conditions and mental health of the Chinese immigrants between 1865-1900 - Ning Anticona, José Li (2016)
This part inquires the presence of mental health disorders in Chinese immigrants (coolies) who came to Peru between 1849 and 1874 as indentured laborers to supply the lack of manpower after the abolition of slavery. Historical publications about how this population lived were reviewed. The main reports were based on historical records from labor places between 1865 and 1900 and let us outline emotional and conduct disorders related to sustained stress (traumatic draft, long and unhealthy sea voyage, life without family, enslaved work and confinement in slave quarters). It is inferred the presence of asthenic states due to somatic diseases, depression, hypochondriasis or simulation in workers called ‘mañosos’ (tricky). Literature refers homosexual practices in this male population in compulsory confinement and sexually transmitted diseases including syphilis; a great consume of opium, not replaced by alcohol or coca; hopelessness; resistance and revolt attitudes; suicides; homicides; group revolts and collaborationism during the Pacific War. These historical findings confronted with hospital statistics of the Manicomio del Cercado (part I) coincidently point out high opium consume, diagnosed in the hospital as ‘toxic psychosis’ associated with this narcotic. There is a discrepancy between historical reports of frequent sexually transmitted diseases, including syphilis and the low hospital prevalence of general paresis, the psychiatric form of neurosyphilis. This incongruence is discussed and the possibility of an ecological malariotherapy as an influencing factor on the low hospital prevalence of general paresis is proposed.